Sociedade Contemporânea e Cuidados Paliativos: a morte e o morrer no campo da saúde - Marinho, Suely Oliveira (2005)
This work refers to a qualitative exploratory research that aims to investigate some aspects that mark the experience of death in modernity, as it s growing social disqualification and concealment, and more recently, in the period known as contemporary, their greater visibility in field of specialized knowledge in order to evaluate how these issues materialize in the field of health care. This discussion will serve as a basis for reflection on the new model of care called palliative care, which has meant an attempt to humanize the care given to patients with advanced disease not possible to cure or a terminal phase of life. For this part of an analysis of historical overview of modes on the ways the issue of death is presented in the twentieth century, and the process of emergence of new care model being discussed the concepts of "modern death" - which reflects an objectification Death by scientific technical knowledge in the medical field - and "contemporary death or neomoderna" - which arose as a reaction to the latter characterized mainly by claiming the right to die with dignity. To perform the specific objectives, namely, to know a palliative care service in the routine of a hospital, map their main characteristics and collect data on the dynamics and organization of the service was performed a brief observation through visits to the Pain Management Program and Palliative Care, in the University Hospital ClementinoFragaFilho, Universidade Federal do Rio de Janeiro (HUCFF / UFRJ). The results showed that in the last 40 years there has been a remarkable change of attitudes and representations associated with end of life. This promoted the emergence of new philosophies and alternative ways to deal with death and dying, that palliative care is the largest representative of this new century, becoming hegemonic in care at the end of life in the professionals in the fields, associative and political. Showed that palliative care have been integrated into the public health system in our country from national policies aimed at the reality of cancer, especially with development in the context of high complexity hospital, still confined exclusively to the domain of the specialist, a fact indicated by ignorance the clientele about the existence and nature of the service.